2021
DOI: 10.32535/ijabim.v6i2.1026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quality Care on Patient Loyalty Mediated with Patient Satisfaction and Moderated by Age and Gender (Study in Outpatients at a Private Hospital)

Abstract: An increasingly competitive business climate and changes in patient behavior, fostering hospital managers to pay more attention in regard to factors that could affect patient loyalty. Quality care is well known as a major contributor to patient loyalty. The purpose of this study is to examine the effect of quality care on patient loyalty with patient satisfaction as the mediating variable, while age and gender as the moderators. This research model was tested empirically in outpatients at a private hospital. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The findings of this study are in line with a similar study on obstetric services in hospitals conducted by Yeo et al (2021), where patient satisfaction has a significant effect on patient loyalty. The results of this study are also in line with previous studies conducted in different countries and different types of hospitals (Ricca & Antonio, 2021;Liu et al, 2021;Tan et al, 2019) where it was found that a positive evaluation of patient satisfaction at the hospital would encourage his intention to be loyal to the hospital.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study are in line with a similar study on obstetric services in hospitals conducted by Yeo et al (2021), where patient satisfaction has a significant effect on patient loyalty. The results of this study are also in line with previous studies conducted in different countries and different types of hospitals (Ricca & Antonio, 2021;Liu et al, 2021;Tan et al, 2019) where it was found that a positive evaluation of patient satisfaction at the hospital would encourage his intention to be loyal to the hospital.…”
Section: Discussionsupporting
confidence: 91%
“…Empirical research on hospital services in general shows that patient satisfaction will have a significant effect on patient loyalty (Fatima et al, 2018;Asnawi et al, 2019;Liu et al, 2021). Research in Indonesia also confirmed that patient satisfaction has been shown to have a significant effect on patient loyalty (Ricca & Antonio, 2021). Research with the concept of experiential satisfaction also shows results when consumer perceptions of experiential satisfaction increase, consumers will show more loyal behavior (Bellio & Buccoliero, 2021).…”
Section: Literature Reviewmentioning
confidence: 86%
“…A theory from Donabedian (1988) explains PS represents the outcome of an interpersonal health care process [2], [28]. According to some of the previous research, the perception of PS toward a health service is known to affect PL, therefore evaluating the factors that affect PS is significantly important to be able to increase PL [17], [19], [20], [29], [30]. To be able to explain the antecedents of PS and its impact on loyalty, this study develops the theory of Mehrabian and Russell (1974) about stimulus organism response.…”
Section: Since 2002mentioning
confidence: 99%
“…The results demonstrate that quality care has a significant positive effect on patient loyalty. Several managerial implications were found for hospital management to increase patient loyalty, especially considering the gender of the patient in providing services (Ricca & Antonio, 2021). (Katuuk et al, 2019) Balanced Scorecard approach as a strategic management tool can improve the quality of strategy implementation, when it can clarify the size of its strategic performance.…”
Section: Literature Reviewmentioning
confidence: 99%